Plato’s Theory of Mimesis in the Cratylus: from Ideal Language to Ordinary Language - Liangxin Sun (Problemos)
This article reinterprets the theory of mimesis in the Cratylus, exploring how language functions as an image that imitates its objects. Contrary to prevailing studies contending that Socrates fails to reconcile naturalism and conventionalism, this article argues that Socrates proposes a form of naturalism that acknowledges the role of convention. This naturalism reveals that human language has a dual nature by demonstrating the relation between images and originals. Through instrumentalism and sound-symbolism, Socrates envisions language as an ideal instrument for imitating the Forms of things, whereas the difference between images and originals leads to inevitable falsehood in the establishment and use of ordinary language. The real purpose of the theory of mimesis is to defend the possibility of knowledge and language by opposing the sophists’ doctrine of flux.